Bagaimana Persepsi Memengaruhi Keputusan - Angga Jibrilda Syahrial; Dhio Gusti Miranda; Muhamad Davy Kemalludin; Pinkan Ade Sefiana; Mada Aditia Wardhana (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This study examines the role of perception in individual and organizational decision-making through a Systematic Literature Review (SLR) and content analysis approach. Perception is understood as an internal process that shapes understanding of objects, influencing preferences and decisions. Contextual factors such as culture, socio-economics, and technology also contribute to shaping perception. This study adopts a theoretical framework in which perception mediates the relationship between external attributes—such as price, quality, and brand image—and final decisions. By analyzing 993 scholarly articles from 2021 to 2025, this research maps perception models in consumer and organizational domains and identifies research gaps related to the integration of digital factors such as algorithms and AI. The validation process was conducted through triangulation between AI-generated prompts and human-based thematic analysis. The results highlight the need for perception models to adapt to digital dynamics and emphasize the importance of ethical integration in modern decision-making systems.